Improved atopic dermatitis accompanied by pompholyx - Emi Murakami; Satoshi Morioke; Akio Tanaka (Frontiers Media S.A., 2024)
In the treatment process of atopic dermatitis, pompholyx may occurs on palms and soles. However, there is limited knowledge about which patients are more likely to develop pompholyx and when it is expected to occur. Therefore, this study investigated the occurrence of pompholyx after the start of induction remission treatment. We collected medical information from 48 AD patients who visited Hiroshima University Hospital for the first time between January 2019 and December 2020, from the time of their first visit to 12 months later. In the initial group of 48 patients, 10 individuals developed pompholyx within 1 year after their first visit. There was no clear connection between the occurrence of pompholyx and treatment received. Most of the patients who developed pompholyx were above the age of 30. Serum thymus and activation-regulated chemokine (TARC) levels tended to be higher at the first visit in the group that later developed pompholyx compared to the group that did not. In conclusion, patients over the age of 30 with higher serum TARC levels may develop pompholyx while their AD is improving. It is crucial to provide these patients with information about the possibility of developing pompholyx during the course of their AD treatment and that it would be cured in the course of treatment.